Aves no campus da UFT em Arraias - TO - Oliveira, Janeide Pereira de (Universidade Federal do Tocantins, 2022)
The purpose of this study was to identify the birds that appear on the UFT Campus in Arraias, and indicate the importance of this group for the preservation of the environment, and analyze the possibility of implementing Environmental Education projects and bird watching. The field work registered 63 species distributed in 27 families, with a predominance of species with feeding habits (trophic guild) omnivorous, insectivorous, granivorous and frugivorous. This is an initial work, which should guide other studies with greater sampling effort, involving other environmental variables and bird characteristics. Until there are more studies on birds on the Campus, it is suggested to propose Environmental Education and Bird Watching activities with a more restrictive, simple character, starting with the involvement of the local community, planning short trails, manuals, and primers.